POTENTIAL TEST OF GREEN BETEL (PIPER BETLE L.) LEAF EXTRACT CREAM IN COMBINATION WITH BASIL LEAF EXTRACT (OCIMUMSANCTUM L.) AS ANTI-ACNE - Ummu Kalsum; Nurfiddin Farid; Nurul Inayah; Muhammad Arman (Universitas Muhammadiyah Magelang, 2021)
Acne problem is the most common problem that many people fight for. Even though is not a dangerous thing, but that problem will make the sufferer feel unconfident. Acne vulgaris is an inflammatory disorder with blockage and accumulation of the Keratin materials that caused by Propionibacterium acnes bacteria. Now on, Herbal plant is the most selected one as an acne treatment because of the lack effect for the sufferer than a medical treatment. The plants are Basil (Ocimum sanctum L.) and green Lemongrass (Piper Betle L.). Both of them have a Saponin and Flavonoid as an antimicroba. Therefore, in this research will combine that two of the plants which is then formulated in to the cream form. The cream formulation made with 3 different concentration variances were 15%, 30% dan 45%. The type of the research is an in vitro of experimental research method. Where the cream formula making process done by manually and to measure that inhibition to Propionibacterium acnes bacteria. That in the concentration of 15% has an inhibition 20.02 mm, the concentration of 30% was 21.24 mm and the concentration of 45% was 25.05 mm. Inhibition zone > 20 mm categorized as very strong inhibition. So that, could be conclude the cream Basil Leaf Extract (Ocimum sanctum L.) in combination with Green Betle Leaf Extract (Piper Betle L.) had a potential and most effective concentration as an anti-acne was the third formulation (45% concentration) with an inhibition was 25.5 mm and categorized as a very strong inhibition to Propionibacterium acnes.